Interplay between Supply Chain Visibility and Cyber Security Performance - Gani, Anisha Banu Dawood; Fernando, Yudi; Tseng, Ming-Lang (Asia Pacific Industrial Engineering & Management Systems, 2021)
Manufacturing industry is highly targeted and susceptible to cyberattacks given its interconnected and global supply chain that is rich with design, customer, and financial data. Hence, this study was undertaken to examine if the cyber supply chain risk management (CSCRM) practices adopted by firms can protect their supply chain from intrusions and how effective their practices are in securing their CSC. In addition, the role of CSC visibility as a mediator in achieving CSC performance was also tested. A survey method was used to gather data from E&E manufacturing firms that were registered with Federation of Malaysian Manufacturers (FMM). A total of 130 respondents’ data was analyzed using IBM SPSS 24 and PLS SEM 3.3.3 tools to answer the research objectives stipulated. This study managed to prove empirically the integral role a dedicated governance team can bring into setting the security tone within its CSC. The result from the study also confirms the significant role that CSC visibility plays in achieving CSC performance. Moreover, there is also a strong direct relationship between CSC visibility and CSC performance as theorized, giving affirmations to manufacturing firms that investments and policies devised to improve CSC visibility will fare well in a secure supply chain. Thus, manufacturing firms need to fully evaluate its network perimeter and prioritize integration effort and governance of standards and policies that would improve its visibility among its supply chain partners, both internally and externally. Inherently, this implies assessing the cybersecurity maturity level of its supply chain partners, beyond first tier suppliers, in their ability to protect integrated devices and remote-access connections from being exploited.